Surface barrier discharges for Escherichia coli biofilm inactivation: Modes of action and the importance of UV radiation. - Breno A B Salgado; Stefania Fabbri; Aaron Dickenson; Mohammad I Hasan; James L Walsh (PLoS ONE, 2021)
Cold plasma generated in air at atmospheric pressure is an extremely effective antimicrobial agent, with proven efficacy against clinically relevant bacterial biofilms. The specific mode of bacterial inactivation is highly dependent upon the configuration of the plasma source used. In this study, the mode of microbial inactivation of a surface barrier discharge was investigated against Escherichia coli biofilms grown on polypropylene coupons. Different modes of exposure were considered and it was demonstrated that the long-lived reactive species created by the plasma are not solely responsible for the observed microbial inactivation. It was observed that a synergistic interaction occurs between the plasma generated long-lived reactive species and ultraviolet (UV) photons, acting to increase the antimicrobial efficacy of the approach by an order of magnitude. It is suggested that plasma generated UV is an important component for microbial inactivation when using a surface barrier discharge; however, it is not through the conventional pathway of direct DNA damage, rather through the synergistic interaction between liquid in the biofilm matrix and long-lived chemical species created by the discharge.